Semantic Similarity/Relatedness for Cross Language Plagiarism Detection - Hanane Ezzikouri; Mohammed Erritali; Mohamed Oukessou (Institute of Advanced Engineering and Science, 2016)
Generally utterances in natural language are highly ambiguous, and a unique interpretation can usually be determined only by taking into account the context in the utterance occurred. Automatically determining the correct sense of a polysemous word is a complicated problem especially in multilingual corpuses. This paper presents an application programming interface for several Semantic Relatedness/Similarity metrics measuring semantic similarity/distance between multilingual words and concepts, in order to use it after for sentences and paragraphs in Cross Language Plagiarism Detection (CLPD); using WordNet for the English-French and English-Arabic multilingual plagiarism cases.